3x+3(x-5)=4x+9

Simple and best practice solution for 3x+3(x-5)=4x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+3(x-5)=4x+9 equation:


Simplifying
3x + 3(x + -5) = 4x + 9

Reorder the terms:
3x + 3(-5 + x) = 4x + 9
3x + (-5 * 3 + x * 3) = 4x + 9
3x + (-15 + 3x) = 4x + 9

Reorder the terms:
-15 + 3x + 3x = 4x + 9

Combine like terms: 3x + 3x = 6x
-15 + 6x = 4x + 9

Reorder the terms:
-15 + 6x = 9 + 4x

Solving
-15 + 6x = 9 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-15 + 6x + -4x = 9 + 4x + -4x

Combine like terms: 6x + -4x = 2x
-15 + 2x = 9 + 4x + -4x

Combine like terms: 4x + -4x = 0
-15 + 2x = 9 + 0
-15 + 2x = 9

Add '15' to each side of the equation.
-15 + 15 + 2x = 9 + 15

Combine like terms: -15 + 15 = 0
0 + 2x = 9 + 15
2x = 9 + 15

Combine like terms: 9 + 15 = 24
2x = 24

Divide each side by '2'.
x = 12

Simplifying
x = 12

See similar equations:

| 3x+11=-38-4x | | -3x-14=8-4x | | -156-7x=52+x | | x^2-5x-72=0 | | -24+4y=-16 | | -78+8x=20+x | | x+6x+x+3-3=19-3 | | 4x-2(x-3)=16 | | -111+4x=89+12x | | -6(x+5)(x+8)=0 | | 11-r=-(2r-3) | | 6x^2+4=520 | | -8=19r/3-2/3(8r+3) | | 7(4b+5)= | | -2x+56-16=16 | | 4g^2+32g=0 | | x-52=-7x+60 | | -4(2x-4)=112 | | -20x+16=-5 | | -2x-35=16+x | | sin(2x)+sin(x)=0 | | 4(w-1)=2w-22 | | 8x-31=32+5x | | 2(7+3u)= | | 7.5=5*2*x | | 3*x+2*3=-4 | | 3(5h+5)= | | -19-8x=7-7x | | Log(3x+4)Log(2)=Log(2x-4)-Log(2) | | sin(5x)=0.6 | | -2x+4=-5x | | 15(3t-2)= |

Equations solver categories